Muslim modernity in postcolonial Nigeria : a study of the Society for the Removal of Innovation and Reinstatement of Tradition. - Kane, O. (BRILL, 2003)
Covers Muslim modernity in a country with the largest single Muslim population in Sub-Saharan Africa. It is devoted to the study of the largest single Muslim fundamentalist organization in postcolonial Sub-Saharan Africa, the Society for the Removal of Innovation and Reinstatement of Tradition.